1997
DOI: 10.3109/10837459709031441
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Operating and Formulation Variables on the Morphology of Spray-Dried Protein Particles

Abstract: The purpose of this research was to investigate the shape and morphology of various spray-dried protein powders as a function of spray-drying conditions and protein formulations. A benchtop spray dryer was used to spray dry three model proteins in formulation with a sugar or a surfactant. Physical characterizations of the powder included morphology (scanning electron microscopy), particle size, residual moisture, and X-ray powder diffraction analyses. A significant change in particle shape from irregular (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 8 publications
9
91
1
Order By: Relevance
“…Specifically, the outlet temperature increased with increasing inlet temperature and decreased with increasing liquid feed rate and atomizing nitrogen flow rate. These trends are consistent with the findings of others [10]. The model was reasonably accurate in predicting the experimental data ( Figure 3) with an R 2 = 0.86.…”
Section: Outlet Temperaturesupporting
confidence: 81%
See 1 more Smart Citation
“…Specifically, the outlet temperature increased with increasing inlet temperature and decreased with increasing liquid feed rate and atomizing nitrogen flow rate. These trends are consistent with the findings of others [10]. The model was reasonably accurate in predicting the experimental data ( Figure 3) with an R 2 = 0.86.…”
Section: Outlet Temperaturesupporting
confidence: 81%
“…Also, when the atomizing nitrogen flow rate is high, the drop exiting the nozzle tends to be smaller, so the resulting dried particle will be smaller. These trends are expected on the basis of established spray-drying theory [1,10].…”
Section: Geometric Particle Sizementioning
confidence: 99%
“…The inlet temperature is usually several tens of degrees higher than the outlet temperature. Determining the temperature variation within a drying chamber revealed that the temperature at 5 cm below the nozzle was much closer to the outlet temperature than the inlet temperature, and that the temperature at 17 cm below the nozzle, midway between the nozzle and outlet, was approximately the same as the outlet temperature (43). This means that during spray drying, droplets in the drying chamber were exposed to the temperature swayed by the outlet temperature.…”
Section: Spray Dr Y For Preparation Of Dr Y Powdermentioning
confidence: 89%
“…The independent variables of spray drying processes are liquid feed rate, atomizing air flow rate, drying air f low rate, and inlet air temperature. Outlet temperature linearly depends on each of these variables (43), suggesting that it can be estimated if the regression lines between outlet temperature and the independent variables are available for a spray drier. The inlet temperature is usually several tens of degrees higher than the outlet temperature.…”
Section: Spray Dr Y For Preparation Of Dr Y Powdermentioning
confidence: 99%
“…At the inlet temperatures were 180 °C and 190 °C have produced microcapsules rough surface and wrinkled. This happens because, at low temperatures, the drying rate would decrease so that the solidification process of microcapsules would take longer [44,45]. Wrinkles microcapsules could be caused by the diffusion of oleoresin from the microcapsules because of slow drying rate.…”
Section: Encapsulation Efficiencymentioning
confidence: 99%